Indirect decompression via oblique lumbar interbody fusion is sufficient for treatment of lumbar foraminal stenosis - Sheng-Chieh, Tseng; Yu-Hsien, Lin; Yun-Che, Wu; Cheng-Min, Shih; Kun-Hui, Chen; Cheng-Hung, Lee; Chien-Chou, Pan (Frontiers in Surgery, 2022)
Oblique lumbar interbody fusion (OLIF) is a popular technique for the treatment of degenerative lumbar spinal disease. There are no clear guidelines on whether direct posterior decompression is necessary or not after OLIF. The purpose of this study was to analyze the effect of the indirect decompression obtained from OLIF in patients with lumbar foraminal stenosis. We retrospectively reviewed 33 patients who underwent OLIF surgery for degenerative lumbar spinal disease between January 1, 2018 and June 30, 2019. The inclusion criteria included patients who were diagnosed with lumbar foraminal stenosis by preoperative MRI. The exclusion criteria included the presence of central canal stenosis, spinal infection, vertebral fractures, and spinal malignancies. The clinical results, evaluated using the visual analogue scale of back pain (VAS-Back), VAS of leg pain (VAS-Leg), and Oswestry disability index (ODI), were recorded. The radiologic parameters were also measured. The VAS-Back, VAS-Leg, and ODI showed significant improvement in both the posterior decompression (PD) and non-posterior decompression (Non-PD) groups postoperatively (all, p < 0.05). Patients in the Non-PD group had better results than those in the PD group in the VAS-Back at 12- and 24-months postoperatively (0.00 vs. 3.00 postoperatively at 12-months, p = 0.030; 0.00 vs. 4.00 postoperatively at 24-months, p = 0.009). In addition, the ODI at 24-months postoperatively showed better improvement in the Non-PD group (8.89 vs. 24.44, p = 0.038). The disc height in both the PD and Non-PD groups increased significantly postoperatively (all, p < 0.05), but the restoration of foraminal height was significantly different only in the Non-PD group. There was no statistically significant difference in cage position, cage subsidence, fusion grade or screw loosening between the PD and Non-PD groups. Indirect decompression via OLIF for lumbar foraminal stenosis showed favorable outcomes. The use of interbody cages and posterior instrumentation was sufficient for the relief of symptoms in patients with lumbar foraminal stenosis. Additional direct posterior decompression may deteriorate results in the follow-up period.